Investor’s Learning Style and Knowledge Acquisition Dimension: The Role of ICT in Maximising Knowledge Acquisition - Muhammad Adlin Saputra; Caraka Hadi (Journal of Accounting and Investment, 2023)
Research aims: This study investigates investor learning style in acquiring knowledge moderated by Information and Communications Technology (ICT).Design/Methodology/Approach: This study performed an online survey method, comprising 263 convergent-type and 210 assimilative-type as the final sample. The Structural Equation Model using Smart-PLS was employed to estimate the relationship of the latent variableResearch findings: The regression results revealed that convergent-type investors positively affected all knowledge acquisition dimensions due to their high experience and knowledge compared to assimilative-type, even with the help of ICT.Theoretical contribution/Originality: This research discloses comprehensive constructs of sophisticated and unsophisticated investors in acquiring knowledge. Widely, it contributes to the literature advancement related to investor learning style, knowledge acquisition, and the role of ICT.Practitioner/Policy implication: It can be used as an ideal individual construct in learning that can be embraced by financial consultants, capital market training institutions, and professional education. Thus, they are also responsible for developing investors' skills, especially novice investorsResearch limitation/Implication: This study did not fully capture the exact participants’ learning styles. Thus, future research is hoped to provide experimental approaches, reaching the natural cause-effect measurement of investor learning style and knowledge acquisition.